2013
DOI: 10.1051/0004-6361/201322522
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-reconnection exhausts in the sheath of magnetic clouds

Abstract: Context. Reconnection exhausts are a common phenomenon in the solar wind. Many exhausts were observed between an interplanetary coronal mass ejection (ICME) and the ambient solar wind, or between two ICMEs, or within the interior of a single ICME. Observed exhausts are almost exclusively associated with ICMEs with low (often much lower than 1) proton beta. Aims. Often the sheath regions of ICMEs have a high level of plasma beta. Therefore we aim to find out whether the reconnection exhausts occur frequently in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Gosling et al (1995) discuss a mechanism in which part of the field lines at the MC periphery are magnetically connected to the outer heliosphere after reconnection occurred. Case studies (Dasso et al 2006(Dasso et al , 2007Feng & Wang 2013) and a statistical analysis of a large sample of events (Ruffenach et al 2015) indicate that an MC can suffer magnetic erosion at its front during its travel in the heliosphere, forming a back region with mixed properties of both MC and ambient solar wind (Dasso et al 2006;Ruffenach et al 2012). Thus, because MCs are 3D structures, it is possible that this erosion only happens at various specific locations along the flux rope.…”
Section: Results For the Average Profilesmentioning
confidence: 99%
“…Gosling et al (1995) discuss a mechanism in which part of the field lines at the MC periphery are magnetically connected to the outer heliosphere after reconnection occurred. Case studies (Dasso et al 2006(Dasso et al , 2007Feng & Wang 2013) and a statistical analysis of a large sample of events (Ruffenach et al 2015) indicate that an MC can suffer magnetic erosion at its front during its travel in the heliosphere, forming a back region with mixed properties of both MC and ambient solar wind (Dasso et al 2006;Ruffenach et al 2012). Thus, because MCs are 3D structures, it is possible that this erosion only happens at various specific locations along the flux rope.…”
Section: Results For the Average Profilesmentioning
confidence: 99%
“…18h their beta distribution is biased to β < 2 and magnetic reconnection may occur during higher plasma beta conditions if the shear angle of the magnetic field across the current sheet is sufficiently large (Phan et al 2013). Indeed, Feng and Wang (2013) found five reconnection exhausts within a high-beta sheath of an MC observed on 18-20 October, 1995.…”
Section: Sheath Signatures and Propertiesmentioning
confidence: 99%
“…The neighbourhood of the sheath-ICME boundary is a much less studied region in terms of plasma wave activity. The accumulation of plasma and magnetic field from different sources during the interplanetary formation of the sheath introduces interfaces that are suitable places to find plasma discontinuities and reconnection exhausts (e.g., Kataoka et al 2005;Feng and Wang 2013). Magnetic reconnection favours low plasma beta conditions (β < 2) (e.g., Scurry et al 1994).…”
Section: Sheath Signatures and Propertiesmentioning
confidence: 99%
“…Obviously, more event studies are needed to confirm these findings. However, previous studies have also shown that compressions can trigger reconnection in the sheath of interplanetary coronal mass ejections (Feng & Wang, ) or in the Earth's magnetotail (Vörös et al, ).…”
Section: Introductionmentioning
confidence: 99%